Electrospraying and Electrospinning in Drug Delivery : Principles, Methods, and Applications - Mulham Alfatama; Abid Mehmood Yousaf; Abd Almonem Doolaanea; Yasser Shahzad (CRC Press, 2026)
Electrospraying and electrospinning have emerged as powerful techniques for the fabrication of drug-loaded nano- and microstructures, offering precise control over particle size, morphology, and drug release kinetics. Electrospraying and Electrospinning in Drug Delivery provides a comprehensive overview of the principles and latest advancements, methodologies, and applications of electrospraying and electrospinning techniques in the field of drug delivery. It encompasses a wide array of topics, including but not limited to targeted drug delivery systems, controlled release formulations, stimuli-responsive materials, and biomedical applications.• Describes the most recent and successful applications of electrospraying/electrospinning in drug delivery• Covers fundamental principles, instrumentation, process parameters, and optimization strategies• Delves into the diverse range of materials employed in electrospraying and electrospinning, such as polymers, ceramics, and metals, highlighting their unique advantages and applications in drug delivery• Explores the incorporation of functional additives, such as nanoparticles and biomolecules, to tailor the properties and performance of electrospun/electrosprayed drug delivery platformsBy compiling contributions from leading experts in the field, this edited volume fosters interdisciplinary collaboration and inspires further research endeavors. The book will serve as a valuable resource for researchers, academicians, and professionals interested in understanding and utilizing these innovative techniques for enhanced drug delivery systems.